2014
DOI: 10.1161/atvbaha.114.303290
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Platelet Nitric Oxide Production by Nebivolol Prevents Thrombosis

Abstract: H ypertension is associated with an increased risk of arterial thrombotic events, such as stroke and myocardial infarction, 1 in which platelets are deeply involved. Previous studies have shown that β-adrenoceptor blockers reduce platelet activation and aggregation, 2 but this does not seem to be a class effect because not all β-blockers share this property. 3 dl-Nebivolol (a racemic mixture of d-and l-nebivolol) is a third-generation β 1 adrenoceptor-selective antagonist that, besides its β-blockade-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…16 In fact, it has been demonstrated that platelet-derived NO affects platelet adhesion at intermediate and high shear and that the production of NO in platelets is dominated by receptormediated interactions at low-intermediate shear and by mechanotransduction at high shear. 9,38,50 In our experimental conditions, platelet adhesion and thrombus formation onto a collagen surface under flow conditions take place in only a few minutes with the contribution and interplay of different receptors like GPIb-V-IX, GPVI, a 2 b 1 , the purinergic receptors P2Y 1 and P2Y 12 , and a IIb b 3 which, to a different extent, regulate the global increase of intracytoplasmic Ca 11 .…”
Section: Blood 22 January 2015 X Volume 125 Number 4 Platelet Nitrimentioning
confidence: 92%
See 4 more Smart Citations
“…16 In fact, it has been demonstrated that platelet-derived NO affects platelet adhesion at intermediate and high shear and that the production of NO in platelets is dominated by receptormediated interactions at low-intermediate shear and by mechanotransduction at high shear. 9,38,50 In our experimental conditions, platelet adhesion and thrombus formation onto a collagen surface under flow conditions take place in only a few minutes with the contribution and interplay of different receptors like GPIb-V-IX, GPVI, a 2 b 1 , the purinergic receptors P2Y 1 and P2Y 12 , and a IIb b 3 which, to a different extent, regulate the global increase of intracytoplasmic Ca 11 .…”
Section: Blood 22 January 2015 X Volume 125 Number 4 Platelet Nitrimentioning
confidence: 92%
“…In agreement with this hypothesis, mice with only circulating platelets deficient of eNOS and with a normal endothelium showed a shortened bleeding time upon endothelial damage. 39 The preeminent role of platelet-instead of endothelium-derived NO in the antithrombotic activity of DL-nebivolol previously reported 12 further suggests that NO generated by platelets upon activation at an arterial damage site is more effective than that generated by endothelium-derived NO in preventing thrombosis, probably because it acts exactly where platelets become activated. 12 These different roles would explain why the endothelial NO response to shear must be an immediate and continuous reaction, whereas platelet NO production would occur only "on demand" and when the initial hemostatic process has already taken place.…”
Section: Blood 22 January 2015 X Volume 125 Number 4 Platelet Nitrimentioning
confidence: 98%
See 3 more Smart Citations